How robust are Holocene treeline simulations? A model-data comparison in the European Arctic treeline region - Fang, Keyan; Morris, Jesse L.; Salonen, J. Sakari; Miller, Paul; Renssen, Hans; Sykes, Martin; Seppa, Heikki (Journal of Quaternary Science, 2013)
Treeline encroachments and retractions can provide global-scale feedbacks to the climate system, and treeline dynamics are therefore of great relevance for understanding global climate variability. To assess the accuracy of long-term treeline simulations based on the generalized dynamic vegetation model LPJ-GUESS, we simulate European Arctic treeline dynamics over the past 9000 years and compare the results with fossil-based reconstructions. The results show that while LPJ-GUESS is limited in its ability to capture species-level current treeline patterns and past dynamics, it is generally able to realistically simulate the Holocene coniferous treeline changes with a cutoff biomass carbon of 2 C kg m(-2). The model captures the northward expansion of the boreal forest during the mid Holocene and correctly simulates a treeline retreat in response to climate cooling during the last 3000 years. However, there are data-simulation disagreements particularly during the early Holocene, which mainly result from the differences between the two palaeoclimate model scenarios used to drive the simulations. We suggest that the spatial accuracy of the model could be improved by incorporating the influence of topographic features, the extent of the Arctic peatlands, the tree species life-history characteristics, microclimate and other ecological factors. Copyright (c) 2013 John Wiley & Sons, Ltd.